Too polluted to work? The gendered correlates of air pollution on hours worked - Guillermo Montt (IZA Journal of Labor Economics, 2018)
Air pollution affects workers' ability to work by damaging their own health, but also by damaging the health of their dependents. This paper draws on 20 years of air pollution and employment data from Santiago, Chile, a highly polluted metropolis, particularly in fall and winter months. The paper finds that though air pollution is not associated to a reduction in overall hours worked, it does so for women and particularly for women with children. Weeks with pollution at 100 μg/m3, common for Santiago, see double the gender difference in working hours. It is hypothesised that children, unable to go to school, must stay home and cared for. These findings suggest that air pollution may contribute to gender inequality through the gendered-biased distribution of care responsibilities. Pollution brings to evidence gender inequalities in care and, given the gendered nature of care and the geographic distribution of pollution, may contribute to enhance gender and geographic labour market inequalities. Environmental policy may serve to enhance gender equality as well.
Keywords: J22; Q52; Q53; 330; Air pollution; Hours worked; Health; Care; Gender